Protein and peptide biopharmaceuticals: An overview - Agyei, D.; Ahmed, I.; Akram, Z.; Iqbal, H.; Danquah, Michael (2017)
© 2017 Bentham Science Publishers. Bioactive proteins and peptides are recognised as novel therapeutic molecules with varying biological properties for potential medical applications. Development of protein and peptidebased therapeutic products for human use is growing steadily as they continue to receive an increasing rate of approval by the United States Food and Drugs Administration (US FDA). In this short review, we describe the current status and methodologies involved in the synthesis of protein and peptide biopharmaceuticals with an emphasis on the drivers and restrains to their exploitation in the therapeutic products sector.